Document Management System (DMS) Arsip Digital, Manajemen Versi Dokumen, Persetujuan Elektronik di PT Home Center Indonesia Retail (Informa Sawangan) - Zainal Abidhin; Titik Oktaviani; Wasis Haryono (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The rapid growth of digital documents in organizational environments demands a reliable and structured system for managing document storage, version control, and approval workflows in an efficient and secure manner. This research develops a Document Management System (DMS) equipped with versioning and electronic approval features to improve overall document lifecycle processes at PT Home Center Indonesia Retail (Informa Sawangan). The system was developed through the Software Development Life Cycle (SDLC) methodology, consisting of requirements analysis, system design, implementation, and comprehensive testing stages. Several Unified Modeling Language (UML) diagrams including use case, activity, sequence, and Entity Relationship Diagram (ERD) were used to represent and clarify the system model and its functional processes. The results show that the implementation of the DMS significantly increases operational efficiency, accelerates document retrieval time, improves version tracking accuracy, and enhances transparency and accountability in approval workflows. Overall, the findings provide valuable insight into effective digital document governance and can serve as a practical reference for future system development and implementation in similar organizational environments.